STRUCTURING DEFENSE POLICIES FOR THE DEFENSE AND CONTROL OF STRATEGIC NATURAL RESOURCES - DE PAULA, GABRIEL (Revista Política y Estrategia, 2018)
During the last decade, there has been a reconfiguration of a new geopolitical scenario. This new scenario focus on the assessment about strategic natural resources (oil, gas and water, and less important, biodiversity, food and fertile land) and its spatial condition (the resources are in a territory which is politically defined by boundaries or zone of influence). The scenario in South America is not far from that international dynamic, which affects in different levels the strategic lines of national defense policies in Brazil, Venezuela and (in less degree) Argentina. In that way, competence and confluence scenarios are defined, which may have variability in the conflict level, such as a military confrontation or cooperation mechanisms (as the South America Defense Council). These scenarios are geographically located in: oil and gas basins, Amazonas, water resources, Antarctica, Atlantic Ocean and fertile land. The defense strategies set parameters for the design of the armed forces, as far as the hypothesis of conflicts above-mentioned applied. Thus, the defense administration reconfigured the capabilities of the Armed Forces (logistic, personnel, doctrine, resources, surveillance), in order to achieve the mission of control the regions where availability of natural resources exists. A nivel global, se viene reconfigurando durante la última década un nuevo escenario geopolítico, que tiene como criterio ordenador la valoración de recursos naturales estratégicos (especialmente hidrocarburos y agua, y en menor medida biodiversidad, alimentos y tierra fértil) y su espacialidad (en tanto, dichos recursos están en un territorio determinado política y territorialmente). El escenario sudamericano no escapa a esta lógica internacional, la cual influye, con diferentes niveles de intensidad, en la determinación de líneas estratégicas de defensa nacional en Brasil, Venezuela y (en menor medida) la Argentina. Se definen de esta manera escenarios de competencia y de confluencia, los cuales pueden adquirir ...